Upaya Meningkatkan Hasil Pembelajaran Guru Di Kelas Melalui Pemanfaatan Lesson Study Sebagai Komunitas Belajar Untuk Guru Di SMP Negeri 1 Simpang Teritip Tahun Pembelajaran 2021/2022 - Purwestri Madya (STIKes Ibnu Sina Ajibarang, 2023)
Some of the problems that underlie the low quality of education include: Lack of teacher planning in teaching, teachers seem monotonous in carrying out learning activities and are not flexible in responding to current developments in the field of education, and a lack of variety in the learning methods used resulting in a lack of student enthusiasm in learning. This School Action Research (PTS) aims to improve teacher learning outcomes through the use of lesson study as a learning community for teachers in the Classes of SMP Negeri 1 Simpang Teritip for the 2021/2022 academic year. The subjects of the School Action Research are teachers who teach at SMP Negeri 1 Simpang. Teritip, Simpang Teritip District, West Bangka Regency 2021/2022 Academic Year. The results of the research showed that through the use of lesson study as a learning community for teachers in classes at SMP Negeri 1 Simpang Teritip, there was an increase of 21.67% in cycle I and 14.66% in cycle II. In detail, for teacher 1, the initial condition was an average of 53.33, the first cycle averaged 75.00, an increase of 20.00%, the second cycle averaged 91.25, an increase of 16.25%. Teacher 2 initial condition averaged 55.00, first cycle averaged 80.00, increased 25.00%, second cycle averaged 91.25, increased 10.25%. Teacher 3 initial conditions average 50, cycle I average 70, an increase of 20.00%, cycle II average 87.50, increase 17.25%. The results achieved by the teacher have met the target, namely by comparing the results with a minimum increase of 10%. Based on the results of the research above, it can be concluded that through the use of lesson study as a learning community for teachers in classes at SMP Negeri 1 Simpang Teritip, learning outcomes can be improved.